"Fairness" in an unequal society: Welfare workers, labor inspectors and the embedded moralities of street‐level bureaucracy in Argentina. (2nd July 2021) - Perelmiter, Luisina
Abstract: This article advances a new argument on street‐level bureaucrats' (SLBs) moral dilemmas in developing countries. Developing countries feature deeper and more pervasive social and economic inequalities than their developed counterparts. They also feature what I call a fragmented stateness: states whose legal and bureaucratic reach is functional and territorially unequal and that also have an ambiguous relationship with their own legality. This macro‐level force shapes daily bureaucratic encounters and SLBs' moral dilemmas and practices in ways that the literature has not fully grasped. I found that the awareness of this fragmented stateness implies a kind of structural experience of arbitrariness in bureaucratic encounters that makes the exercise of fair judgments in the implementation of policies elusive. I ground my argument in an ethnographic account of bureaucratic encounters in different arenas of the Argentinean social protection system: welfare provision and labor inspection. By reconstructing the connections between fragmented stateness and state workers' moral dilemmas, this article presents a novel and empirically grounded theoretical argument on an often‐overlooked dimension of collective regulation of conflicts and judgments at the state frontlines.